2022
DOI: 10.3390/bios12020110
|View full text |Cite
|
Sign up to set email alerts
|

Review of Microdevices for Hemozoin-Based Malaria Detection

Abstract: Despite being preventable and treatable, malaria still puts almost half of the world’s population at risk. Thus, prompt, accurate and sensitive malaria diagnosis is crucial for disease control and elimination. Optical microscopy and immuno-rapid tests are the standard malaria diagnostic methods in the field. However, these are time-consuming and fail to detect low-level parasitemia. Biosensors and lab-on-a-chip devices, as reported to different applications, usually offer high sensitivity, specificity, and eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 101 publications
1
8
0
Order By: Relevance
“…Haemozoin has been demonstrated in early ring stages [ 25 ], but inability to detect the ring stages by Gazelle could reflect a lower haemozoin concentration in young parasitic stages, as identified elsewhere [ 26 , 27 ]. Other haemozoin detection systems have claimed detection of P. falciparum at parasite densities below 40 parasites/uL at the ring stage [ 28 , 29 ]. Gazelle’s sensitivity and specificity for diagnosis of low densities of P. vivax has also been shown to be similar to microscopy and better than RDTs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haemozoin has been demonstrated in early ring stages [ 25 ], but inability to detect the ring stages by Gazelle could reflect a lower haemozoin concentration in young parasitic stages, as identified elsewhere [ 26 , 27 ]. Other haemozoin detection systems have claimed detection of P. falciparum at parasite densities below 40 parasites/uL at the ring stage [ 28 , 29 ]. Gazelle’s sensitivity and specificity for diagnosis of low densities of P. vivax has also been shown to be similar to microscopy and better than RDTs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to microscopy, RDTs, and UMTs, there are several emerging diagnostic techniques that will likely have a role in future comprehensive malaria programs. These include magnetic resonance relaxometry, 32,33 magnetic deposition microscopy, 34 novel photoacoustics, 25 biosensors and lab-on-a-chip techniques, 35 and multiomics-based sensors. 36 Apart from these, there are new techniques that function with the aid of machine learning; these include rapid and object classification using lowfield nuclear magnetic resonance (NMR) relaxometry, 37 hemozoin-based techniques, 38 spectroscopy-based techniques such as impedance spectroscopy, terahertz spectroscopy, 39 and whole-genome sequencing.…”
Section: Degree Of Agreement Between Blood Smear Microscopy and Umtsmentioning
confidence: 99%
“…Unfortunately, currently available tools are either poorly adapted to field settings, such as the highly sensitive nucleic acid amplification-based tests, or are limited in detecting low-level infections and other important features such as parasitemia quantification or species identification. Several methods have been targeting prompt and accurate malaria diagnosis, and despite the fact that quite promising approaches have been developed, there is still room for improvement. ,,, Overall, this work proves, by fully characterizing RBCs infected with P. falciparum parasites, that optical absorbance and reflectance spectrophotometry are promising measurement techniques, allowing competitive and accurate malaria diagnosis, with limits of detection below that of the gold standard diagnosis, and, additionally, allowing the stage differentiation between rings and trophozoites, which has never been reported before.…”
Section: Discussionmentioning
confidence: 58%
“…In fact, our research team has previously explored the properties of hemoglobin and synthetic hemozoin crystals (without cultured P. falciparum parasites) and demonstrated that this could have the potential for malaria diagnosis. ,, Thus, herein, as a following step, we intend to explore the potential of the optical properties of natural hemozoin. For that purpose, a commercial setup was used to fully characterize the optical absorbance and reflectance properties of in vitro cultured P.…”
mentioning
confidence: 99%
See 1 more Smart Citation